MENGATASI ADIKSI MAKANAN DENGAN METODE MEDITASI VISUALISASI DAN PROVOKASI: LAPORAN KASUS - Willie Japaries; Frisca Desma; Rudi Suryana; Selamat Rodjali; Lianah The (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
Objective: This is to share clinical experience in treating addiction to ‘soto’ food with meditative visualisation and provocation method. Method: Subject is an adult male suffering from addiction to soto for the last 5 years. He was treated as out patient. He was instructed to visualize the addicted food, being feeded into his mouth, chewed as usual, but not swallowed. Then he was instructed to visualize the soto food had been mixed with saliva and transformed so as not delicious anymore. On the second session, provocation was done using the real soto food, the same sequence was repeated. Patient was instructed to look in details the addicted soto food had turned into a disgusting thing. Results: After 2 sessions of treatment, each about 60 minutes, with one day interval, patient confessed free from soto addiction. The effect was durable at 6 months follow up. Conclusion: The meditative visualisation-provocation therapy is effective in treatment of food addiction within two days.